Artificial Intelligence, Blockchain, Machine Learning, and Customer Relationship Management - Maria Joy I. Idian; Mohummad Kamrul Hassan; Akaa Samuel Terzungwe (Bincang Sains dan Teknologi, 2023)
This article discusses the utilization of technology, particularly artificial intelligence (AI) and blockchain, in customer relationship management (CRM). The use of technology in CRM helps companies improve customer experience, maximize customer value, and make better business decisions. AI plays a crucial role in managing CRM by collecting, analyzing and personalizing customer data, predicting customer decisions, and creating chatbots. Blockchain improves the transparency, security and accuracy of customer information stored in CRM. Research data shows that the combination of AI and blockchain in CRM can lead to increased business efficiency, improved customer experience, revenue increase, improved data security and increased transparency of customer information.